Javaserver faces 2.0 essential guide for developers - Vohra, Deepak (Cengage Learning PTR, 2015)
JavaServer Faces is one of the world's most commonly used frameworks for building user interfaces on the Web. In JavaServer Faces 2.0: Essential Guide for Developers, expert Java programmer and Web developer Deepak Vohra covers all the new features of JavaServer Faces 2.0 using examples in Oracle JDeveloper and the integrated Oracle WebLogic Server. The book covers all aspects of Web application development with JSF 2.0, including setting up the environment for an application, using the JDeveloper wizards and the Component palette, and running a sample application. Additionally, the book is suitable for preparing for the Java EE 6 JavaServer Faces Developer Certified Expert Exam (Exam Number: 1Z1-896). Ideal for pro-level developers and intermediate trainees, this book covers everything from Facelets and Ajax to resource handling, client behaviors, system events, and more. Build your expertise with JavaServer Faces 2.0 today, with JavaServer Faces 2.0: Essential Guide for Developers